Influence of adaptive energy saving techniques on office buildings located in cities of the Iberian Peninsula - Bienvenido-Huertas, David (2021)
The use of setpoint temperatures based on adaptive comfort algorithms is a method more and more used as an energy saving technique. Knowing the relationship between inhabitable rooms with their specific climate is crucial for users' climate adaptation, especially in a global warming context. This research analyses the influence of EN 15251:2007, EN 16798-1:2019, and ASHRAE 55-2017 standards on an office building located in 65 cities. The effects of climate change have been considered in the energy performance of current, 2050, and 2100 scenarios. Also, 780 dynamic simulations were performed so that a cluster analysis was carried out to determine the similarity relationships among the various zones. The results show that the model of the EN 16798-1:2019 standard was the option achieving a greater energy saving in current and future scenarios, and the use of energy was greatly reduced in those zones characterized by having a greater cooling energy consumption. Moreover, the differences of energy consumption between the adaptive models in the cities and years generated that the clusters presented differences among all cities, so such scenarios are required to be considered for future interventions. This research is the transition towards the goals proposed by the European Union for 2050.